(untitled) (Journal of the Bangladesh Agricultural University, 2018)
An experiment was conducted to evaluate the growth performance of silver carp (Hypophthalmichthys molitrix) in cage stocking at different densities. It was expected that silver carp could grow feeding on plankton without external feeding. In this experiment, silver carps in nine cages were stocked in three different stocking densities such as 20, 30 and 40 fishes/m3 designated as treatments T1, T2 and T3, which were located in the south west corner of the L-shaped pond in Field Laboratory Complex, Faculty of Fisheries, Bangladesh Agricultural University (BAU), Mymensingh consisting of three treatments with three replications of each for a period of 90 days from 18th August to 17th November, 2015. Each cage size was 1m x 1m x1m (length x width x height) and silver carp was cultured in the cage with natural feed which filtered phytoplankton mainly. Twenty five genera of phytoplankton were identified in pond and the average phytoplankton production was around 8.44x105cells/liter. Water quality parameters such as temperature, dissolved oxygen, pH and transparency were recorded fortnightly. At the completion of the experiment, weight showed significant difference (p>0.05) among three treatments although length didn’t vary significantly. The highest length gain (18.61+0.369 cm) and the highest weight gain (62.52+2.249 g) were found in T1. The highest SGR% for silver carp was found in T1 and the highest total production was obtained in T3 (5.00+ 0.015 kg/m3). Individual growth performance of silver carp was satisfactory. Further studies are needed with different stocking densities and duration to verify the result. J. Bangladesh Agril. Univ. 16(2): 322-327, August 2018